Theorizing rituals: annotated bibliography of ritual theory, 1966-2005 - Kreinath, Jens; Snoek, Joannes A. M.; Stausberg, Michael (Studies in the history of religions, 2007)
Primary literature (442 items) --Secondary literature (82 items) --Lexicon articles (96 items) --Readers (8 items) --Bibliographies (5 items).